Greenland, Sefstroms Glacier at Scoresby Land, now Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1933)
The lower of the two "mystery" lakes on the north side of Fraenkel Land with the Jatte Glacier, completely filling the valley, and Miss Boyd Land in the background. Icebergs calve off the side of Jatte Glacier into this lake and large stranded bergs are seen on the shore many feet from the present water level. August 17, 1933. (Caption from Boyd, L. A. (1934). Further Explorations in East Greenland, 1933. Geographical Review, 24(3), 475.) Sefstroms Glacier